An analysis of thermo-mechanical fatigue crack growth in the titanium alloy Ti-6246 - Palmer J.; Jones J.; Whittaker M.; Williams S. (MATEC Web of Conferences, 2020)
Titanium alloys are equipped with impressive high strength and low density, along with other notable mechanical properties. Often the choice for low to intermediate temperature mechanical applications, titanium alloys are well utilised within the aerospace industry, making up 40% of the aero-engine. Within the gas turbine engine, the high transient thermal stresses developed due to variations in power requirements during a typical flight cycle give rise to the phenomenon of thermo-mechanical fatigue (TMF). The lifing models utilised within this research focus on damage tolerance approaches. TMF crack growth test techniques have been developed for high performance titanium alloys, in which diverse phasing (φ) between mechanical loading and temperature have been investigated. In addition, factors affecting the TMF behaviour of Ti-6246, including peak temperature, minimum temperature and temperature range have also been explored.